Pengaruh Lingkungan Kerja Positif terhadap Motivasi dan Kinerja Sumber Daya Manusia di Desa Cicalengka Kecamatan Pagedangan Kabupaten Tangerang - Ariyanti, Eti; Wardani, Endang Susilo; Irawati, Laila (Jurnal PKM Manajemen Bisnis, 2025)
A positive work environment plays a crucial role in enhancing the motivation and performance of human resources, especially in rural community settings. This community service activity aimed to examine the influence of a positive work environment on the motivation and performance of human resources in Desa Cicalengka, Kecamatan Pagedangan, Kabupaten Tangerang. The implementation took place at the Desa Cicalengka Office on May 5, 2024. The activity was conducted by 12 lecturers from Universitas Pamulang and involved 27 local community members as participants. The methods applied included material presentation, practical exercises, discussions, and question-and-answer sessions. The PKM activities were systematically carried out through stages of planning, execution, and reporting. Results from the activity indicated that fostering a positive work environment significantly improved participants’ motivation and overall work performance. Community members showed increased enthusiasm, commitment, and cooperation in their respective roles after participating in the program. This improvement is expected to contribute to sustainable development and better governance in the village administration. The findings highlight the importance of continuous community empowerment efforts focused on creating supportive and motivating workplace conditions. Future programs are recommended to maintain and further develop these positive environmental factors to ensure long-term benefits.